2016
DOI: 10.1177/0394632016648707
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomy of drugs used in the treatment of actinic keratoses

Abstract: Actinic keratosis (AK) represents an emerging issue in the area of skin diseases which undergo high risk for developing squamous cell carcinoma (SCC). Recently, evidence has been accumulated that 3% diclofenac sodium and ingenol mubetate may efficiently counteract the development of progressive AK even if the pharmacoeconomic impact of such a treatment remains poorly defined. With the objective of assessing the efficacy of 3% diclofenac sodium versus ingenol mebutate, a comparative cost-efficacy analysis was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…As there was little difference in quality-adjusted life-years per patient between the two treatments, the analysis interpreted this as an additional cost of €19.65 to treat a patient with ingenol mebutate, with no additional benefit over diclofenac by assuming equal efficacy. 23 These findings diverge from previous publications on the relative efficacy and cost-effectiveness of ingenol mebutate. However, we offer a critique of this new pharmacoeconomic analysis.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…As there was little difference in quality-adjusted life-years per patient between the two treatments, the analysis interpreted this as an additional cost of €19.65 to treat a patient with ingenol mebutate, with no additional benefit over diclofenac by assuming equal efficacy. 23 These findings diverge from previous publications on the relative efficacy and cost-effectiveness of ingenol mebutate. However, we offer a critique of this new pharmacoeconomic analysis.…”
Section: Discussioncontrasting
confidence: 64%
“…A pharmacoeconomic analysis of 3% diclofenac sodium versus 0.015% ingenol mebutate in the treatment of AK, from an Italian Healthcare System perspective, reported that diclofenac was more cost-effective than ingenol mebutate. 23 Estimated total costs over 12 months for treating 500 patients with diclofenac were €82.594 versus €95.416 for ingenol mebutate. As there was little difference in quality-adjusted life-years per patient between the two treatments, the analysis interpreted this as an additional cost of €19.65 to treat a patient with ingenol mebutate, with no additional benefit over diclofenac by assuming equal efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also initiates apoptosis through activation of bcl-2 and caspase 8 [ 19 ]. There are new studies about effectiveness of diclofenac in AK treatment [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study highlights the importance of cost considerations when a treatment decision is made. Other analyses were mainly based on decision tree models using previously published data, which may not be sufficient to reproduce the treatment costs in a real‐world setting . Nevertheless, the generalizability of the results is limited as costs for topical drugs and reimbursement modalities are highly variable in a country‐specific context .…”
mentioning
confidence: 99%